Lessons from Land Administration Projects : A Review of Project Performance Assessments - Independent Evaluation Group (World Bank, Washington, DC, 2016)
Land rights and the systems that administer them can vary significantly across the world and within countries (World Bank 2003). For a number of reasons, land rights may be unclear or insecure. Securing land rights plays an important role in driving economic growth and poverty reduction. In recent years there has been increasing awareness of the relevance of land tenure issues to food security, climate change, rapid urbanization, informality, and indigenous peoples’ rights. The World Bank Group has a long history of developing and implementing projects aimed at securing land rights through a variety of interventions. This note synthesizes cross-cutting findings from 14 Independent Evaluation Group assessments of land administration projects that the World Bank has supported from 1998 to 2014. The project-level assessments reviewed for this report contain a wealth of information about how the Bank Group approached different problems related to strengthening land administration systems in diverse environments. This information is relevant to both land administration specialists and experts in other fields whose work is impacted by land tenure issues.